KUALITAS PELAYANAN PEMBUATAN SURAT KETERANGAN CATATAN KEPOLISIAN (SKCK) DI KEPOLISIAN RESOR KAHAYAN HILIR KABUPATEN PULANG PISAU - Pasaribu, Muhammad Irvan Yazid Azhar (Jurnal Riset Akuntansi Politala, 2025)
This study aims to determine the quality of police certificate issuance services at the Kahayan Hilir Police Station in Pulang Pisau Regency. The research method used is qualitative, employing Zeithaml, Panasuraman, and Berry's theory in Hardiansyah, which includes tangibility, reliability, responsiveness, assurance, and empathy. The data collection techniques used in this study include observation, interviews, and documentation. Based on the research findings, the quality of service is already quite optimal and maximal. However, there are several shortcomings that need to be addressed, including the presence of staff who are not fully responsible for the tasks assigned to them, as well as limited knowledge, which is one of the factors hindering the performance of staff.